Defining Global Benchmarks for Laparoscopic Liver Resections: An International Multicenter Study. Issue 4 (15th April 2023) - Goh, Brian K.P.; Han, Ho-Seong; Chen, Kuo-Hsin; Chua, Darren W.; Chan, Chung-Yip; Cipriani, Federica; Aghayan, Davit L.; Fretland, Asmund A.; Sijberden, Jasper; D'Silva, Mizelle; Siow, Tiing Foong; Kato, Yutaro; et al.
Abstract : Objective: To establish global benchmark outcomes indicators after laparoscopic liver resections (L-LR). Background: There is limited published data to date on the best achievable outcomes after L-LR. Methods: This is a post hoc analysis of a multicenter database of 11, 983 patients undergoing L-LR in 45 international centers in 4 continents between 2015 and 2020. Three specific procedures: left lateral sectionectomy (LLS), left hepatectomy (LH), and right hepatectomy (RH) were selected to represent the 3 difficulty levels of L-LR. Fifteen outcome indicators were selected to establish benchmark cutoffs. Results: There were 3519 L-LR (LLS, LH, RH) of which 1258 L-LR (40.6%) cases performed in 34 benchmark expert centers qualified as low-risk benchmark cases. These included 659 LLS (52.4%), 306 LH (24.3%), and 293 RH (23.3%). The benchmark outcomes established for operation time, open conversion rate, blood loss ≥500 mL, blood transfusion rate, postoperative morbidity, major morbidity, and 90-day mortality after LLS, LH, and RH were 209.5, 302, and 426 minutes; 2.1%, 13.4%, and 13.0%; 3.2%, 20%, and 47.1%; 0%, 7.1%, and 10.5%; 11.1%, 20%, and 50%; 0%, 7.1%, and 20%; and 0%, 0%, and 0%, respectively. Conclusions: This study established the first global benchmark outcomes for L-LR in a large-scale international patient cohort. It provides an up-to-date reference regarding the "best achievable" results for L-LR for which centers adopting L-LR can use as a comparison to enable an objective assessment of performance gaps and learning curves.